Accounting System in Small Scale Enterprises: A Case Study - Koperunthevy, K. (Vavuniya Campus of the University of Jaffna., 2008)
This study investigates the accounting system in Small Scale Enterprises in the Vavuniya District. The law has not insisted the small Scale Enterprises to keep the ledgers and financial reports. Therefore, the purpose of the study is to find out the accounting system followed by the Small Scale Enterprises. 124 members of the Chamber of commerce, industry and agriculture are considered as population and using the convenient sample selection method, 42 enterprises are selected. Questionnaires are used to collect the information about the accounting system. The data is analyzed using the Microsoft Excel worksheet. The data analysis has five steps. The first step identifies primary book keeping according to the underlying assumptions and the next step identifies following double entry system to record the primary data and according to that preparation of profit and loss account and balance sheet. The third step sorts out preparation of profit and loss account after making the adjustments. The fourth step sorts out how many enterprises have balance sheet according to the SLAS 3 and the fifth step finds out the preparation of cash flow statement. According to the data analysis in the first step only ten enterprises are selected, the second step sorts out five, the third step again sorts out two, the fourth step finds out one enterprise and in the final step none of the enterprises are qualified. According to the data analysis, the conclusion of the study is drawn. That is the accounting system in the small scale enterprises is not good, but they have prime books to enter the transactions. Therefore, the study concludes that most of the Small Scale Enterprises have single entry accounting system.
Keywords: Small Scale Enterprises; Accounting system; Financial report